Ethical integration of AI in judicial systems: Advancing fairness, transparency, and judicial efficiency - Vukatana, Kreshnik; Hoxha, Elira; Ferhataj, Anxhela (Rivista italiana di informatica e diritto, 2025)
This study assesses the perceived role of Artificial Intelligence (AI) in advancing judicial reform in Albania, with emphasis on efficiency, fairness, and transparency. A survey of 340 students in law, computer science, and computer engineering was analysed using Spearman’s rank correlation to explore how perceived benefits and risks relate to support for AI in justice processes. The findings show a balanced view. Students acknowledge AI’s potential to reduce delays and improve administrative coordination, yet they also express concerns about bias, limited transparency, and relying on automated tools in decisions that affect fundamental rights. They emphasise the need for clear rules, explainable systems, and strong human oversight to ensure responsible use. This research makes a pioneering contribution to understanding how future legal professionals perceive AI in transitional judicial systems, introducing an AI-Driven Justice System Framework based on the study’s findings.Integrazione etica dell’intelligenza artificiale nei sistemi giudiziari: promuovere equità, trasparenza ed efficienza giudiziariaQuesto studio analizza il potenziale dell’IA nel trasformare i sistemi giudiziari, con riferimento al contesto albanese. Un sondaggio su 340 studenti di giurisprudenza e area tecnico-informativa, esaminato tramite correlazione di Spearman, indaga il legame tra benefici e rischi percepiti e il supporto all’IA nei processi giudiziari. I risultati mostrano un cauto ottimismo rispetto alla capacità dell’IA di migliorare efficienza e ridurre i ritardi, insieme a rilevanti preoccupazioni sulla correttezza degli algoritmi impiegati, trasparenza decisionale e necessità di supervisione umana. Questa ricerca contribuisce a chiarire come i futuri professionisti valutino l’integrazione dell’IA nei sistemi giudiziari, introducendo un AI-Driven Justice System Framework elaborato sulla base dei risultati dello studio.